2015
DOI: 10.1074/jbc.m115.662064
|View full text |Cite
|
Sign up to set email alerts
|

Megalin/Cubulin-Lysosome-mediated Albumin Reabsorption Is Involved in the Tubular Cell Activation of NLRP3 Inflammasome and Tubulointerstitial Inflammation

Abstract: Background: NLRP3 inflammasome activation is involved in albuminuria-induced renal injury. Results: The inhibition of megalin/cubilin or lysosomal cathepsin B reduced albuminuria-induced NLRP3 inflammasome activation. Conclusion: Megalin/cubilin and lysosome rupture is involved in albumin-triggered tubular injury and TI. Significance: This study provides novel insights into albuminuria-induced TI and implicates the active control of albuminuria as a critical strategy to halt the progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…reported that albumin overload in PTECs induced a slight increase in megalin and cubilin protein expression at 24 hours, with a marked decrease at 48 hours. The decline was associated with the presence of albumin-induced apoptosis 30 . In human podocytes, we found no such decline in either cubilin or megalin mRNAs and proteins, probably due to the absence of any increase in cell death.…”
Section: Discussionmentioning
confidence: 93%
“…reported that albumin overload in PTECs induced a slight increase in megalin and cubilin protein expression at 24 hours, with a marked decrease at 48 hours. The decline was associated with the presence of albumin-induced apoptosis 30 . In human podocytes, we found no such decline in either cubilin or megalin mRNAs and proteins, probably due to the absence of any increase in cell death.…”
Section: Discussionmentioning
confidence: 93%
“…In several prior studies, NLRP3 can clearly be seen at tubules in human tissue but the relevance of NLRP3 tubular localization has never been addressed by the authors 21 32 . Furthermore, a recent study by Liu’s group demonstrated NLRP3 expression at tubules in albumin overloaded rats 33 . We found that NLRP3 predominantly localized to the tubules with virtually no staining in glomeruli in histologically normal kidney.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have indicated that the NLRP3 inflammasome contributes to albumin-induced lesions in tubular cells [38,39]. Liu et al [40] demonstrated that endocytic receptor-lysosome-mediated albumin reabsorption was involved in the tubular cell activation of NLRP3 inflammasome and tubulointerstitial inflammation. Moreover, studies from Zhuang et al reported that NLRP3 inflammasome mediated albumin-induced renal tubular injury through impaired mitochondrial function [41] and further provided direct evidence indicating the important role of the albumin-NLRP3 inflammasome axis in mediating the impairment of renal tubular tight junctions and integrity [42].…”
Section: Nlrs and Ckdmentioning
confidence: 99%